Land Cover Change Analysis of Ternate Selatan Sub-district, Ternate City in 2014 and 2024 - Philia Christi Latue; Heinrich Rakuasa (Yayasan Adra Karima Hubbi, 2024)
Economic growth, urbanization, and infrastructure development are the main drivers of the increase in built-up land area in Ternate Selatan Sub-district. This study aims to investigate and understand the dynamics of land use evolution over a period of one decade. Using satellite image data and image processing techniques, an analysis was conducted to identify significant changes in land cover, particularly in relation to economic growth, urbanization, and infrastructure development. The results showed an increase in the area of built-up land in Ternate SelatanSub-district from 2014 to 2024 along with changes in land use patterns that reflect development pressure. In 2014, the percentage of built-up land area in Ternate SelatanSub-district was 24.69% and continued to increase in 2024 to 31.44% of the total area of Ternate Island. In contrast to other land cover classes that experienced a decrease in area. The results of this study are expected to provide an important contribution for policy makers, environmentalists, and other stakeholders in designing appropriate measures to maintain the balance between economic growth and nature conservation in Ternate SelatanSub-district.